2020
DOI: 10.24057/2071-9388-2018-73
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of The Syrian Civil War On Land Use / Land Cover In Al-Yarmouk Basin During 2010–2018

Abstract: The study goal is to monitor and evaluate the significant changes in land use/land cover (LULC) in Al-Yarmouk basin (YB) within only 8 year. (YB) is shared between Syria, Jordan, Palestinian Authority, and Israel. (YB) has been affected not only by water scarcity, frequent drought conditions; But nowadays provide proof that the major factor responsible for the current of the significant changes in (LULC) in the study area is the Syrian civil war that began in mid-2011, and the Syrian refugee influx into Jordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…Water bodies experienced a greater de-crease of 60% during the crisis than before (Table 3). This observation is consistent with previous studies that identified the growing population and IDPs, increasing demand for water for domestic use or irrigation, water pollution and mismanagement as the leading causes of this decrease (Al-Husban & Ayen, 2020;Faour & Fayad, 2014;Müller et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Water bodies experienced a greater de-crease of 60% during the crisis than before (Table 3). This observation is consistent with previous studies that identified the growing population and IDPs, increasing demand for water for domestic use or irrigation, water pollution and mismanagement as the leading causes of this decrease (Al-Husban & Ayen, 2020;Faour & Fayad, 2014;Müller et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…This was due to a combination of slow and rapid forces, including the growing local population, the influx of IDPs, the war and the accompanying economic shock. These findings are consistent with previous research identifying similar forces as key drivers of LULCC in Syria during the crisis and before (Abdo, 2018;Abeed et al, 2021;Al-Husban & Ayen, 2020;Cazabat, 2018;Hammad et al, 2018;Heidarlou et al, 2020;Jaafar et al, 2015;Landholm et al, 2019;Mohamed et al, 2020;Mohamed, 2021bMohamed, , 2021aMüller et al, 2016;Rahmoun et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation